(untitled) (Scientific journal of the Fergana State University, 2025)
This article shows the development of the agricultural sector of Uzbekistan during the war and the worthy contribution of the Uzbek people to ensuring victory in the war. It was also analyzed that the Soviet government was trying to further improve its political and economic power in the life of society. Since agriculture has difficult responsibilities, its labor resources and material capabilities have become very problematic. Development of the irrigation system. It was revealed that during the transition of agricultural production to military rails in a very short time, due to the monoculture of cotton, the agricultural network was adapted for the cultivation of raw cotton.